If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + -7 = 3 Reorder the terms: -7 + c = 3 Solving -7 + c = 3 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + c = 3 + 7 Combine like terms: -7 + 7 = 0 0 + c = 3 + 7 c = 3 + 7 Combine like terms: 3 + 7 = 10 c = 10 Simplifying c = 10
| m/(-10)=55 | | 12n=-6n-24n | | f(2)=(3)(2)-2 | | 3eightsp=9 | | -1(5x+5)=0 | | c+7=3 | | 4u-32=-4u | | 4n=356 | | 6(x+4)=11x+5 | | 10x=6y+2 | | -67=-7(-7+x)+5(-4x-7) | | f(-2)=(3)(-2)-2 | | -14.5+1.5y=-31 | | 1.2x^2+2.5x=1.8 | | 90+18x=108 | | -5x+7x-3= | | 9n=333 | | 0.1(a-16)=0.4(a-1) | | b(-8)=(1/14) | | 2y=4y^2-2 | | f(-5)=(3)(-5)-2 | | 4h=-16 | | x=1-7x^2 | | 0=7x^2+36x-36 | | b=-8 | | 227=-7(8n-8)-n | | 4y=3y^2-4 | | 8n=536 | | v/(-3)=(-7/8) | | -20=5m | | 9n=549 | | 11(9-4)=5(p+3) |